Dental fear in children and adolescents: a comparison of forms of anxiety management practised by general and paediatric dentists - Diercke, Katja; Ollinger, Isabelle Stephanie; Lorenzo Bermejo, Justo; Stucke, Kathrin; Lux, Christopher J.; Brunner, Monika (International journal of paediatric dentistry, 2012)
International Journal of Paediatric Dentistry 2011; 22: 60-67 Background. About 11% of children and adolescents suffer from dental fear. These young people run an increasing risk of undergoing more invasive treatments. Aim. We researched the management of dental anxiety in young patients by general and paediatric dentists as well as by trained and untrained dentists. Design. Eight hundred dentists in Germany were interviewed via e-mail regarding their experience, treatment techniques, information material and complications during the treatment of fearful children. We also examined how difficult dentists judge the treatment of anxious children and how often they participate in continuing education courses. Results. Paediatric dentists applied a greater spectrum of management techniques than general dentists. They used more often psychotherapeutic interventions and anxiety assessment questionnaires. Dentists who frequently attend in continuing education courses judged the treatment to be less difficult and also used psychotherapeutic interventions more often. Conclusions. German paediatric dentists and dentists who take continuing education courses utilise a broader range of techniques to manage dental anxiety. They may be eminently suited to treat children with severe forms of anxiety. Therefore, dentists who treat young patients should participate in education programmes so as to reduce both the anxiety of their patients and their own anxiety.